BENTUK PENYAJIAN DAN BENTUK MUSIK RAPA’I PASEÉ PADA MASYARAKAT ACEH DI GAMPONG AWE KECAMATAN SYAMTALIRA KABUPATEN ACEH UTARA - Desi Fitriani (Universitas Negeri Medan, 2017)
This research have purpose ti investigate the existence and the instruments used inRapa’i Pasee art at Gampong Awe Syamtalira subdistrict Nort Aceh regency. Thetheory used in this research including the explanation of the existence, the presentationfrom, explanation meaning of music, music elements, and the organology of musicinstruments.The population in thi research is music group of Rapa’i Pasee that consistof 16 players, they are 2 was called Syekh (leader), and 14 are music players. Thesample in this research is all population that consist 13 persons. The methods used inthis research is observation, interviewed, and documentation. The data processing andanalysis technic used quality deseriptive research type. The interview result showedRapa’i Pasee at Gampong Awe Syamtalira subdistrict North Aceh regency now was sointerested by people. The Rapa’i Pasee was showed as entertainment in some events,usually like independence day or in prophrt Muhammad Saw birthday or to wecome thecountry guests. The instruments used is Rapa’i Pasee (like rebana but in big size). Thepresentation from showed in Rapa’i Pasee played consist 4 chapter (scene), that isSaleum Aneuk Syahi/Cahi, Saleum Aneuk Rakan, Kisah (story) and closing scene.Rapa’i Pasee have own harmony, Rapa’i Pasee have music from one part, two partsnad three parts. Music from one part was sel up in Saleum Rakan and closing scene,two parts in Saleum Aneuk Syahi/Cahi, and three part was set up in Kisah scene